Comparative Study of Paramedian and Midline Incision in Laparotomy for Peritonitis due to Non-traumatic Gastro-intestinal Tract Perforation (Medicine Today, 2024)
Introduction: A prospective observational study was conducted to compare the paramedian incision with midline incision in gastro-intestinal tract perforation. Objectives: To identify better or superior incision which may reduce post operative mortality and morbidity after laparotomy. Materials and Methods: A prospective observational Hospital based study was conducted from January 2009 to June 2009 at department surgery of Shaheed Ziaur Medical College Hospital, Bogura. A total 100 patients of peritonitis due to non-traumatic gastro-intestinal tract perforation were taken for study. Sample were collected by Convenience (purposive) sampling method. Midline incision and Para median incisions were performed as per standard technique. The details of operations, post-operative complications and follow up to be recorded and analyzed. Results: Opening time and closing time in midline incision is significantly less than paramedian (P